Low income is associated with late nephrology referral in Portugal: A retrospective study - Duarte,Rui (2022)
ABSTRACT Introduction: Social disparities in chronic kidney disease are a reality. Low socioeconomic status is associated with increased incidence of chronic kidney disease and overall worse outcomes. In Portugal, similarly to many European countries, a National Health System was established to provide equity in healthcare access, but its impact in specialized chronic kidney disease care is unclear. This study aims to compare the effects of economic insufficiency in referral and overall specialized kidney care in a Portuguese center. Subjects and Methods: Retrospective cohort study evaluating maintenance hemodialysis patients of a Public Portuguese Nephrology Center from 2017 through 2021. Medical records were compared for presence of low-income status, with primary outcome as baseline estimated glomerular filtration rate at Nephrology referral and secondary outcomes as presence of kidney replacement therapy options appointment, timely vascular access assessment and time to dialysis from referral. Results: A total of 212 participants were evaluated, 96 with low-income status. This group presented higher serum creatinine and lower estimated glomerular filtration rate at referral (2.35 vs. 3.29 mg/dl, p<0.001; 27.63 vs. 18.47 ml/min/1.73 m2, p<0.001; respectively). Low-income status associated with absence of kidney replacement therapy options appointment (OR 2.7, 95% CI: 1.44-5.08; p=0.003) and late vascular access evaluation (OR 2.77, 95% CI: 1.55-4.98, p=0.001). Dialysis-free survival analysis revealed shorter time to dialysis in the low-income status group (15.77 vs. 20.71 months, p<0.001) with a higher cumulative incidence in dialysis at 24 months (HR: 2.11, 95% CI: 1.39-3.21, p < 0.001), a difference that was not verified after adjusting for estimated glomerular filtration rate at referral (HR: 1.16, 95 % CI: 0.74 - 1.80, p = 0.53). Conclusion: Low-Income chronic kidney disease Portuguese patients are at risk for late Nephrology referral, an established factor for adverse outcomes. Shorter time to dialysis appears significative in reducing adequate kidney care access, which can be attenuated through education of primary care providers and general population for chronic kidney disease.